Marfa si banii - Puiu, Cristi (Romania : Studioul de Creatie al Ministerului Culturii, 2001)
A road-movie by a young Romanian director. The hero, Ovidiu, is a young man with an entrepreneurial bent who is trying to launch a business selling snacks while still living in his parent's flat in Constanta. Needing cash to get his business off the ground, Ovidiu is more than willing to listen when he's approached by a local crime boss. A package needs to be delivered to Bucharest, for which Ovidiu will be well-paid. Although he does not know what's in the package (and is smart enough not to ask), he packs up his van and hits the road with his girlfriend and another friend. Assuming they're now smugglers, Ovidiu and his friends have to steer clear of police cars, but the law becomes the least of their worries as Ovidiu notices a red car following them.
Keywords: Fiction films